Effect of four serum components on survival of Treponema pallidum and its attachment to rabbit cells in vitro. Issue 1 (February 1986) - Wong, G H; Steiner, B; Graves, S
Abstract : Transferrin and, to a lesser extent, insulin were two components of serum that enhanced the survival of Treponema pallidum in microaerophilic, acellular medium. These two components also enhanced the attachment of T pallidum to baby rabbit genital organ (BRGO) cells in both aerobic and microaerophilic tissue culture systems. Growth hormone and epidermal growth factor marginally enhanced the attachment of T pallidum to BRGO cells.